1964
DOI: 10.1037/h0044351
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and placebos: The effects of instructions upon performance and mood under amphetamine sulfate and chloral hydrate.

Abstract: The experiment reports the effects of appropriate and inappropriate instructions and 2 drugs (.5 g chloral hydrate and 10 mg racemic amphetamine sulphate) on motor performance and mood measures. The Ss were 90 older men randomly assigned to 9 experimental groups. The design used was expansion of a model design involving Drug Disguised groups, Placebo groups (300 mg lactose), an Untreated group, and Amphetamine, Chloral Hydrate, and Neutral instructions. The drugs and placebos were given to the Ss in capsules, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(39 citation statements)
references
References 9 publications
0
39
0
Order By: Relevance
“…Findings from these studies using the open/hidden drug paradigm are supported by investigations that explicitly modulated the expectancy concerning a given drug by verbal instructions (Lyerly et al, 1964;Kirk et al, 1998;Metrik et al, 2009). The detrimental influence of negative expectations on the drug response became, for instance, apparent in a behavioral experimental study by Dworkin et al (1983), who reported a reversal of 716 analgesia by nitrous oxide in dental pain when participants expected the drug to increase awareness of bodily sensations.…”
Section: The Effect Of Placebo Responses On Pharmacological Treatmentioning
confidence: 50%
“…Findings from these studies using the open/hidden drug paradigm are supported by investigations that explicitly modulated the expectancy concerning a given drug by verbal instructions (Lyerly et al, 1964;Kirk et al, 1998;Metrik et al, 2009). The detrimental influence of negative expectations on the drug response became, for instance, apparent in a behavioral experimental study by Dworkin et al (1983), who reported a reversal of 716 analgesia by nitrous oxide in dental pain when participants expected the drug to increase awareness of bodily sensations.…”
Section: The Effect Of Placebo Responses On Pharmacological Treatmentioning
confidence: 50%
“…In several studies, differences were found in self-rated alertness and/or mood among groups ingesting placebos with different suggestions (walacH et al 2002;brodeur 1965;kirscH 1997;lyerly et al 1964;ross et al 1962;zwyGhuizen-dooreNbos et al 1990) and placebos with different perceptual characteristics (blackwell et al 1972). In the study of kirscH & weixel (1988), participants experienced significant changes in perceived alertness and tension but not in relaxation after receiving placebos with deceptive stimulant suggestion.…”
Section: The Placebo Effect: Introductionmentioning
confidence: 99%
“…Research has demonstrated that in addition to perceived changes in internal states, placebos given with proper suggestion could also affect cognitive tasks as well as psychomotor performance either positively (lyerly et al 1964;ross et al 1962;zwyGHuizeN-dooreNbos et al 1990;fraNkeNHauser et al 1963;kirscH & rosadiNo 1993;lieNert 1955lieNert ) or negatively (e.g. walacH et al 2002MoerMaN 2002).…”
Section: The Placebo Effect: Introductionmentioning
confidence: 99%
“…15 At the end of the first week, patients on dextroamphetamine had lost an average of 2.64 pounds while those on the placebo had gained an average of 0.15 pound. At the end of 4 weeks, the mean weekly weight loss of patients who received dextroamphetamine had dropped to 1.16 pounds, while the mean weight loss of placebo patients was only 0.54 pound.…”
Section: Discussionmentioning
confidence: 99%